Effect of sulfates on cement-stabilized lateritic soils - Sheikh, Ahmad Saeed; Moh, Za-Chieh; Jones, John Hugh; Chai Muktabhant (Bangkok : SEATO Graduate School of Engineering, 1967)
This thesis describes the results of research undertaken to study the effect of sulfates on three cement-stabilized lateritic soils. Sulfates can be expected to affect the strength of soil-cement in two ways: (1) when sulfate-bearing water comes in contact with the soil cement after curing, and (2) when sulfates are present in the soil it(S1 (Bself. It was found that all soil-cement mixtures studied, when soaked in solutions of magnesium and sodium sulfates, underwent a decrease in strength. The amount of decrease was found to depend upon the concentration of the solution. The calcium sulfate solution had different effects on different soils. It was also observed that mixtures made from sulfate-resistant cement, or treated with additives, were less susceptible to attack by sulfate solutions. In case of soils containing sulfates, it was found that the presence of sulfates (of the order of 1-Normal concentration in the molding water) did practically no harm to the strength development of soil-cement. In fact, when present in small quantities, the sulfates increased the strength at low cement concentrations, thus proving to be beneficial.s
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in the SEATO Graduate School of Engineering, Bangkok, Thailand.
Thesis (M.Eng.) - SEATO Graduate School of Engineering, 1967
Keywords: Soil cement